Conformational dynamics modulate the catalytic activity of the molecular chaperone Hsp90 - Sophie L. Mader (Nature Portfolio, 2020)
The chaperone Hsp90 uses the free energy from ATP hydrolysis to control the folding of client proteins in eukaryotic cells. Here the authors provide mechanistic insights into how its catalytic activity is coupled to conformational changes by combining large-scale molecular simulations with NMR, FRET and SAXS experiments.